Parenting With Style: Altruism and Paternalism in Intergenerational Preference Transmission - Doepke, Matthias; Zilibotti, Fabrizio (Econometrica, 2017)
We develop a theory of intergenerational transmission of preferences that rationalizes the choice between alternative parenting styles (as set out in Baumrind1967). ParentsmaximizeanobjectivefunctionthatcombinesBeckerian altruism and paternalism towards children. They can affect their children’s choices via two channels: either by influencing children’s preferences or by imposing direct restrictions on their choice sets. Different parenting styles (authoritarian, authoritative, and permissive) emerge as equilibrium outcomes, and are affected both by parental preferences and by the socioeconomic environment. Parenting style, in turn, feeds back into the children’s welfare and economic success. The theory is consistent with the decline of authoritarian parenting observed in industrialized countries, and with the greater prevalence of more permissive parenting in countries characterized by low inequality.